Applicability of the local interaction model for determining nonlinear-compressible soil resistance to sphere penetration - Kotov, Vasiliy Leonidovich; Balandin, Vladimir Vasilievich; Linnik, Elena Yurievna; Balandin, Vladimir Vladimirovich (Computational Continuum Mechanics, 2012)
The non-stationary processes of impact and penetration of a rigid sphere into nonlinear compressible soil have been investigated taking into account the surface and internal friction of soil. Compressibility of soil is described by the known impact adiabat. The wave mechanism of formation of the force of resistance to penetration of a blunt body of revolution into soil is formulated in relation to the coefficient of lateral earth pressure and the adiabatic impact parameters. A fairly good agreement is achieved between the results of two-dimensional calculations and the local interaction model used to determine the maximum resistance force in the problem of spherical cavity expansion. It is shown that the condition for the applicability of one-dimensional models is violated at the quasi-stationary stage of penetration of spherical projectiles.
Keywords: local interaction model; spherical cavity expansion problem; Grigoryan model; impact adiabat; internal friction; impact; penetration; resistance force